The Connectivity of South Asian Cities in Infrastructure Networks - Derudder, Ben (Taylor and Francis, 2013)
This map summarizes information on the connectivity of 67 important South Asian cities concerning infrastructure networks. The map combines four information layers to reveal a city's overall stature in the region's infrastructure networks, i.e. rail, road, air, and information technology networks. Three dimensions of connectivity are shown: edge thickness reflecting tie strength between pairs of cities; node size reflecting a city's betweenness centrality; and node color reflecting the dominant geographical orientation of a city's connections. A threshold is used for the edges to ensure the map does not appear clogged. The map shows that major connections tend to be within-country linkages between large cities. There are five communities in South Asia's urban infrastructure networks, which largely follow national borders. Delhi, Mumbai, Lahore, Karachi, Chennai, Colombo and Dhaka are shown to be important nodes for the infrastructural integration of South Asia, as these cities mediate flows between relatively unconnected communities and cities.